Defining the undetectable: The current landscape of minimal residual disease assessment in multiple myeloma and goals for future clarity. (March 2021) - Diamond, Benjamin T.; Rustad, Even; Maclachlan, Kylee; Thoren, Katie; Ho, Caleb; Roshal, Mikhail; Ulaner, Gary A.; Landgren, C. Ola
Abstract: Multiple Myeloma, the second most prevalent hematologic malignancy, yet lacks an established curative therapy. However, overall response rate to modern four-drug regimens approaches 100%. Major efforts have thus focused on the measurement of minute quantities of residual disease (minimal residual disease or MRD) for prognostic metrics and therapeutic response evaluation. Currently, MRD is assessed by flow cytometry or by next generation sequencing to track tumor-specific immunoglobulin V( D )J rearrangements. These bone marrow-based methods can reach sensitivity thresholds of the identification of one neoplastic cell in 1, 000, 000 (10 −6 ). New technologies are being developed to be used alone or in conjunction with established methods, including peripheral blood-based assays, mass spectrometry, and targeted imaging. Data is also building for MRD as a surrogate endpoint for overall survival. Here, we will address the currently utilized MRD assays, challenges in validation across labs and clinical trials, techniques in development, and future directions for successful clinical application of MRD in multiple myeloma.